Species composition and microhabitats of frogs within Arakan Valley Conservation Area, Cotabato, Mindanao Island, Philippines - Delima, Elsa May M. (Banwa, 2006)
Species composition and microhabitats of frogs in the Arakan Valley Conservation Area in Cotabato, Mindanao, with three interconnected mountain ranges, were documented using belt transect sampling. Frogs were sampled at 4 sites - one on Mt. Mahuson, two on Mt. Sinaka and one within the Kabalantian-Binoongan mountain range. Twenty-five frog species in 15 genera representing 5 families (Bufonidae, Megophryidae, Microhylidae, Ranidae and Rhacophoridae) were recorded, 9 of which are reported vulnerable. Fourteen species in 4 families were Philippine endemics, 9 of which are restricted to the Mindanao faunal region. Most species were encountered on ground microhabitats although majority of the individuals were seen on arboreal microhabitats. Overlaps in microhabitat use were also observed. Further, 56% of the species were observed on forest edges. The high percentage of endemism may strengthen the importance of this site for conservation and the observed existence of species near edges might also highlight the conservation of all types of habitat.